Colloid cyst of the third ventricle - Asaad El Bakkari; Ittimade Nassar (PAMJ Clinical Medicine, 2020)

(untitled)
We report the case of a male aged by 35-year-old with a history of chronic positional headache, besides he presented an unconscious collapse. The physical and neurological exams find no abnormality, the electroencephalogram and the fundoscopic exam were normal, in front of that we conduct a cerebral CT who shown a well-defined rounded lesion at the roof of the third ventricle spontaneously hyperdense (A). Colloid cysts are rare congenital and benign intracranial tumors, representing up to 0.5 to 1% of all intracranial neoplasms, the middle age of manifestation is between 30 and 50 years-old with sex ratio. They usually occur in the anterior and anterosuperior part of the third ventricle. The cysts may obstruct the foramen of Monroe and as a result impeded cerebrospinal fluid flow is responsible of hydrocephalus with lateral ventricle dilatation. Usually asymptomatic, the clinical presentation is related to the hydrocephalus and growth intracranial pressure responsible for headaches and intracranial hypertension, rarely a sudden death can occur related to an acute hydrocephalus or cardiovascular failure due to abrupt disturbance in hypothalamic function. Cross-sectional imaging usually enables the diagnosis. On all modalities, colloid cysts appear as a rounded well defined, sharply demarcated lesion at the foramen of Monro, which ranges in size from a few millimeters to 3-4 cm. In CT he is typically hyperdense rarely isodense and hypodense and the calcification are uncommon. The treatment of colloid cysts is surgical, he is indicated in symptomatic and huge lesions, encompasses three techniques: stereotactic aspiration mostly used, endoscopic fenestration and microsurgical approach.